Azerbaijan : Issues and Options Associated with Energy Sector Reform - World Bank (Washington, DC, 2012)
The energy sector plays a significant role in the overall economy of Azerbaijan, as in other transition countries, and the World Bank's experience suggests that without energy sector reform and financial viability the transition process is much more difficult and delayed. The objective of this report, therefore, is to outline the issues and options facing Azerbaijan as it develops and implements its agenda for reform of the energy sector in order to inform the country's dialogue on this subject and the associated decision making process. The report focuses on seven key topics: Oil Revenue Management; The Petroleum Sector; The Gas Sector; The Power Sector; The Regulatory Environment; Energy and the Environment; And Social Issues in the Energy Sector. Each section of the report can be read as a stand-alone document; as a result there is some duplication between sections. Each section includes a summary followed by a more detailed discussion of the issues and options. Moreover three appendices are included. The first discusses the factors influencing oil prices, the second outlines the liberalization process and the regulatory models adopted for the gas sector in a number of locations and the third summarizes The State Program for the Development of the Fuel and Energy Sector of the Azerbaijan Republic (2005 - 2015).